2019
DOI: 10.31557/apjcp.2019.20.7.2209
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil to Lymphocyte Ratio Predicts the Response to Neoadjuvant Chemotherapy in Luminal B Breast Cancer

Abstract: Objective: Tumor response to neoadjuvant chemotherapy (NAC) in breast cancer (BC) patients is a predictor for overall survival. The aim of our study was to determine a relationship between the neutrophil to lymphocyte ratio (NLR) prior to NAC, BC subtypes and the probability of a pathologic complete response (pCR). Materials and Methods: Medical records were collected retrospectively from Centro de Cancer at Red Salud UC-Christus. Clinical data collected included peripheral blood cell counts, BC subtype at dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
(22 reference statements)
0
12
1
Order By: Relevance
“…In a meta-analysis, a high NL ratio was shown to be statistically significantly associated with poor response to NAC in breast cancer patients [47]. Rivas and colleagues have shown the NL ratio might be a predictive biomarker for tumor response in luminal B breast cancer patients receiving neoadjuvant therapy [48]. Conversely, we did not find a statistically significant association between NLR, SII, and PLR and tumor response to neoadjuvant therapy.…”
Section: Discussioncontrasting
confidence: 71%
“…In a meta-analysis, a high NL ratio was shown to be statistically significantly associated with poor response to NAC in breast cancer patients [47]. Rivas and colleagues have shown the NL ratio might be a predictive biomarker for tumor response in luminal B breast cancer patients receiving neoadjuvant therapy [48]. Conversely, we did not find a statistically significant association between NLR, SII, and PLR and tumor response to neoadjuvant therapy.…”
Section: Discussioncontrasting
confidence: 71%
“…One of them found that NLR had a statistically significant relationship with the probability of PCR for luminal B subtype. While for the ER positive HER2 negative ones, PCR was not an independent feature for a better survival (34,35). After systematical and thorough analysis, maybe LMR is more suitable for the ER positive, HER2 negative subgroup.…”
Section: B C Amentioning
confidence: 99%
“…In addition, since lymphocytes are critical in cancer immune surveillance and neutrophils have been reported to play a protumor role in most studies, low lymphocytes and high neutrophils in circulation may also suggest immunosuppression status ( 10 ), and studies focused on the relationship between neoadjuvant chemotherapy (NCT) and the NLR might support the above hypothesis. A comprehensive review of the existing reports shows that most studies have found that a low NLR indicates a higher NCT response and pathological complete response (pCR) rate ( 25 27 ); in addition, the NLR has showed predictive value not only in all molecular types of BC but also in both operable and locally advanced BC ( 18 , 28 , 29 ). Interestingly, although Suppan et al did not find a significant correlation between the initial NLR and prognosis, the same cohort revealed a low NLR as a significant parameter for predicting chemotherapy response ( p = 0.012) ( 23 ).…”
Section: Prognostic Value Of the Neutrophil-to-lymphocyte Ratio (Nlr)mentioning
confidence: 99%